Endoscopic placement of covered versus uncovered self-expandable metal stents for palliation of malignant gastric outlet obstruction. Issue 7 (22nd November 2020) - Yamao, Kentaro; Kitano, Masayuki; Chiba, Yasutaka; Ogura, Takeshi; Eguchi, Takaaki; Moriyama, Ichiro; Yamashita, Yukitaka; Kato, Hironari; Kayahara, Takahisa; Hoki, Noriyuki; Okabe, Yoshinobu; Shiomi, Hideyuki; et al.
Abstract : Objective: Stenting is an established endoscopic therapy for malignant gastric outlet obstruction (mGOO). The choice of stent (covered vs uncovered) has been examined in prior randomised studies without clear results. Design: In a multicentre randomised prospective study, we compared covered (CSEMS) with uncovered self-expandable metal stents (UCSEMS) in patients with mGOO; main outcomes were stent dysfunction and patient survival, with subgroup analyses of patients with extrinsic and intrinsic tumours. Results: Overall survival was poor with no difference between groups (probability at 3 months 49.7% for covered vs 48.4% for uncovered stents; log-rank for overall survival p=0.26). Within that setting of short survival, the proportion of stent dysfunction was significantly higher for uncovered stents (35.2% vs 23.4%, p=0.01) with significantly shorter time to stent dysfunction. This was mainly relevant for patients with extrinsic tumours (stent dysfunction rates for uncovered stents 35.6% vs 17.5%, p<0.01). Subgrouping was also relevant with respect to tumour ingrowth (lower with covered stents for intrinsic tumours; 1.6% vs 27.7%, p<0.01) and stent migration (higher with covered stents for extrinsic tumours: 15.3% vs 2.5%, p<0.01). Conclusions: Due to poor patient survival, minor differences between covered and uncovered stents may be less relevant even if statistically significant; however, subgroup analysis would suggest to use covered stents for intrinsic and uncovered stents for extrinsic malignancies.